Quality Control Analysis of Side Member Assy RR Floor Product Using the Statistical Quality Control Method at PT XYZ - Sulaeman, Benyamine; Fransisca Debora; Dewi Ayu Lestari; Marizka Putri Ismawaty; Dian Andini (Jurnal Serambi Engineering, 2026)
Quality control is a critical aspect of the manufacturing industry to ensure that every product meets the specified requirements. PT XYZ, as an automotive component manufacturer, faces the problem of a high number of defective products in the Side Member Assy RR Floor component. This study aims to analyze the quality control process using the Statistical Quality Control (SQC) method with the Seven Tools approach. The research methods include data collection through observation and documentation, followed by analysis using tools such as control charts, checksheets, histograms, Pareto diagrams, scatter diagrams, fishbone diagrams, and flowcharts. The results show that the dominant type of defect is spatter, accounting for 83.7% of total defects. Control chart analysis indicates that the process is not fully under control, as evidenced by data points falling outside the control limits. Fishbone analysis reveals that the main causes of defects originate from non-standardized work methods and insufficient operator skills. As a concrete improvement measure, Standard Operating Procedure (SOP) documents and Visual Inspection Checklist forms were developed. This study provides a tangible contribution by assisting the company in improving product quality and systematically reducing defect rates.